Pervasive Computing in IoT (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
In the era of Internet of Things (IoT) that we have entered, the “Monitoring–Decision–Execution” cycle of typical autonomic and automation systems is extended to include distributed developments that might scale from a smart home or greenhouse to a smart city, and from autonomous driving to emergency management. In such highly distributed and scalable architectures, each of the three processes can be situated at any physical or virtual computing system and located, ideally, at any place. Hence, communication and interoperation between the subsystems that comprise the total IoT system, namely extreme edge, edge, fog, and cloud deployments, are of critical importance. This reprint presents a collection of high-quality, state-of-the-art research papers, each introducing challenging issues in pervasive computing across the different domains of the IoT ecosystem. It comprises four papers focusing on customized application frameworks, three papers dealing with issues of ambient intelligence and assisted living of the aging population, three papers considering blockchain technology in various IoT applications, and two survey papers related to sensors and their applications.